2013
DOI: 10.1103/physreve.88.022813
|View full text |Cite
|
Sign up to set email alerts
|

Slow epidemic extinction in populations with heterogeneous infection rates

Abstract: We explore how heterogeneity in the intensity of interactions between people affects epidemic spreading. For that, we study the susceptible-infected-susceptible model on a complex network, where a link connecting individuals i and j is endowed with an infection rate β ij = λw ij proportional to the intensity of their contact w ij , with a distribution P (w ij ) taken from face-to-face experiments analyzed in Cattuto et al. (PLoS ONE 5, e11596, 2010). We find an extremely slow decay of the fraction of infected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 26 publications
2
46
0
1
Order By: Relevance
“…However, apart from the heterogeneity of degree distribution, the heterogeneity of weights on edges makes the CHMF theory be hard to accurately describe the spreading dynamics on weighted networks [30]. To solve this question, we develop an edge-weight based compartmental theory, which is inspired by Refs.…”
Section: A Spreading Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, apart from the heterogeneity of degree distribution, the heterogeneity of weights on edges makes the CHMF theory be hard to accurately describe the spreading dynamics on weighted networks [30]. To solve this question, we develop an edge-weight based compartmental theory, which is inspired by Refs.…”
Section: A Spreading Dynamicsmentioning
confidence: 99%
“…The HMF theory assumes that the nodes of the same degrees will show the same dynamical characteristics [15,31,32], and can only qualitatively understand the effects of heterogeneous structural properties on quenched networks [24,30]. Similar to the HMF theory, the analytical results derived from the percolation theory will also obviously deviate from the numerical results in the case of strong structural heterogeneity [21], which is caused by the strong dynamic correlations between two connected nodes [33].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically existing studies found that promoting the spreading dynamics could induce distinct critical phenomena with different outbreak thresholds and critical exponents [8]. Practically speaking, promoting the spreading dynamics could shed some lights on the propagation of information [9][10][11], marketing management [12,13], disease spreading [14][15][16][17][18], etc. Many strategies for promoting spreading dynamics have been proposed, such as choosing influential seeds [19,20] and designing effective contact strategies [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, individuals are represented as nodes on a network and their interactions by edges [13][14][15]. Analytical solutions arising from the graph theory [16,17] and percolation [18,19] or simulations can be used to answer questions concerning the potential for a particular disease to invade the population and persist there [20,21], the relationship between the network structure and rate of spread [22][23][24], the future course of an unfolding epidemic [25], and, finally, to assess control strategies that either prevent the disease from invading [26] or aim at its eradication [27][28][29]. Network models are particularly suitable for the latter task, as they allow to represent spatial aspects of the disease spread [30,31] and, therefore, help in designing responsive and local control strategies that target particular individuals or their connections [32].…”
Section: Introductionmentioning
confidence: 99%